The Implementation of Blood Donor Policy of the Indonesian Red Cross in Pontianak City - Suvento Suvento; Lina Sunyata (Fakultan Ilmu Sosial dan Ilmu Politik Universitas Tanjungpura, 2023)
ABSTRACTHigh demand for blood with insufficient blood supply in fulfilling the blood demand can cause problems in people's lives. Various kinds of diseases and actions that really need blood are, ofcourse, inseparable from the availability of blood which must be sufficient in order to create a society that cares about human values. Indonesian Red Cross (PMI) of Pontianak City as a place where people can donate their blood certainly has an important role in solving the needs for blood and the availability of blood is higher than the need for blood. The purpose of this research is to describe the implementation of blood donation in Pontiankan City by UTD PMI of Pontianak City. In the process of this study, the researcher used the theory of policy implementation by Van Horn and Van Meter, which explained that the successful implementation process was caused by six factors. By using this type of exploratory research method with a qualitative approach, the researcher has conducted field research. The results showed that the implementers understood the contents of the policy and the goals of the blood donation policy, implementation resources were an obstacle in conducting the implementation of the blood donation policy, inadequate outreach was also a factor in not having enough blood at UTD PMI of Pontianak City, and inter-organizational communication needs to be expanded and improved massively so that blood donation can be done in more places. Apart from that issue, there was also the attitude of the implementers who tend to be not optimally implemented the blood donation policy. Keywords: Blood needs, blood availability, blood donation, implementation of blood donation.